From climate risk to resilience: Unpacking the economic impacts of climate change in Zambia - Detelinova, Iva; Thomas, Timothy S.; Tian, Junyan; Hammond, Wole; Arndt, Channing (International Food Policy Research Institute, 2023)
Climate change is projected to cause an increase in average temperatures in Zambia and a decline in rainfall, particularly in the southern and western regions. The country experiences high rainfall variability, which climate change is expected to exacerbate, resulting in likely higher frequency and intensity of already reoccurring extreme weather events, such as droughts and floods. The combined effect of the temperature and precipitation projections is anticipated to cause a decrease in water availability at national level and to adversely affect the Zambezi, Kafue, and Luangwa River Basins. Overall, these trends will exacerbate existing vulnerabilities in southwestern Zambia, as the region is already prone to droughts (as well as floods in some parts). On the other hand, the northern parts of the country are projected to experience a slight increase in rainfall and to be overall relatively positively affected by climate change. The key sectors most likely to be significantly affected by climate change in Zambia include agriculture, road infrastructure, and energy. In agriculture, the key risk stemming from climate change is the projected lower maize yields, as this is the country’s staple crop. Other crops are also expected to be adversely affected by higher temperatures, reduced rainfall, and increased occurrence of extreme events, particularly in southern and western Zambia. That said, changing climate conditions could create new agricultural opportunities in the north. Climate change is projected to negatively affect the livestock subsector, which will increase food security risks, particularly for subsistence farmers. In road infrastructure, the projected higher occurrence of flooding, especially in Lusaka Province, could have a knock-on effect for the rest of the economy, particularly if it damages key international corridors passing through this region and/or affects domestic supply chains. Zambia is significantly reliant on hydropower and is already experiencing severe power cuts due to drought. The risks in the sector are exacerbated by the location of key hydropower plants in the southern parts of the country and the projected drying up of main river basins. The electricity shortages have spillover effects on the rest of the economy, including the copper industry, Zambia’s key export. This has international implications, as Zambia is a top copper producer worldwide, and demand for copper is expected to increase significantly due to its crucial role in various green technologies. Thus, absent adaptation measures, the adverse impact of climate change in Zambia could affect global mitigation efforts and strategies.